(3Yde GdGbJUGO aj GdfXe GdhVYjI hGdTQjYI GdGSdGejI (B/s - (3YWhj, ahRjs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2005)
(3jVe JMQje GdQHG aj GdeLJeYGJ GdbOjeI, GdeYJGedGJ GdeUQajI Hjf GdaGFOI hGdQHG, GdbQGQGJ GdeLeYjI GdGSdGejI HTCf GdaGFOI hGdHfhc GdGSdGejI, GdeYGedGJ GdeUQajI hGdHOGFd GdGSdGejI, GdMdhd GdGSdGejI GdHOjdI, SjGSI GdHfc GdGSdGej aj eLGd GdJhXja hGdGSJKeGQ, GdUfGOjb GdGSdGejI, GdHfhc GdGSdGejI eTGcd hMdhd, GdHfc GdGSdGej(B: (3Hfc GdeSJbHds
(3HHdjhZQGajG(B: (3U(B.629-639s
Keywords: (3GdGbJUGOs; (3GdTQjYI GdGSdGejIs; (3Gdabg GdGSdGejs